Normal Values of Third Ventricular Width of Preterm Infants - Koc, Ayse Selcan; Mert, Mustafa Kurthan (Acta Medica, 2019)
Objective: Although the third ventricle width reference ranges obtained by cranial ultrasonography in term infants are known in the literature but there are no adequate and up to date data regarding the reference ranges of third ventricle width in premature infants. In our study, we aimed to obtain the normal reference values of third ventricle width and the third ventricle related parameters in preterm infants (gestational age <32 weeks). Materials and Methods:In our study 156 preterm infant and 64 term infants were included. Weights and head circumference of all infants were measured before C-US. The right and left lateral ventricle anterior horn width (AHW), ventricular index (VI) and third ventricle width were recorded in C-US. Study data were divided into 2 groups as term infants and preterm infants. Results:Third ventricle measurement was successfully performed in all infants. The frequency of cesarean section was significantly higher in preterm infants, while weight and head circumference were significantly lower (p<0.05). R-AHW, L-AHW, R-VI, L-VI was significantly higher in term infants than in preterm infants (p<0.05). Mean ± SD, median, minimum and maximum third ventricle diameters were 1.27±0.33mm, 1.20mm, 0.50mm and 1.90mm respectively in preterm infants. In univariate analysis, GA, R-AHW, L-AHW, R-VI, L-VI values were found to be associated with third ventricle diameters. Linear regression analysis revealed that only GA and R-AHW were independently associated with third ventricle (beta: 0.611 - p<0.001 and beta: 0.141 - p = 0.011, respectively). Conclusion:The third ventricle width obtained by C-US is significantly lower in preterm infants than in term infants and this is independently associated with GA. These results of our study are important for the detection of third ventricle dilatation in preterm infants with abnormal C-US and our data’s were thought to be used clinically.